Dryland river restoration via carnivore reintroduction: Nonnative fauna dominate diets of river otters reintroduced to the Upper Rio Grande. (September 2022) - Wolf-Gonzalez, Gabriela A.; Murphy, Sean M.; Springer, Matthew T.; Cox, John J.
Abstract: Dryland rivers often harbor abundant populations of nonnative species that threaten native fauna and negatively alter ecosystem structure and function. Native semiaquatic carnivores, such as river otters ( Lontra canadensis ), that could predate nonnative fauna have been extirpated from many dryland rivers. During 2008–2010, river otters were reintroduced to the Upper Rio Grande (URG), a principal dryland river in the arid southwestern USA that has been colonized by dozens of nonnative fish and invertebrates. We conducted a scat-based food habits study and investigated whether otter reintroduction could be useful for managing nonnative aquatic fauna via predation. Across seasons, nonnative crayfish and fish were the dominant prey items in otter scats; crayfish frequency of occurrence was highest (61–95%), followed by nonnative suckers (7–26%) and trout (3–28%). After accounting for heterogeneous sampling effort between seasons, multi-level models estimated 0.77–0.93 probabilities that scats contained crayfish, compared to 0.05–0.21 and 0.03–0.14 probabilities for suckers and trout, respectively. Reintroducing river otters, and possibly other semiaquatic carnivores, to degraded dryland rivers might be an effective conservation action for controlling nonnative faunal populations within the biomic approach to river restoration, which could reestablish trophic cascades that improve ecosystem structure and function. Highlights: Dryland rivers are critical freshwater ecosystems in arid landscapes. Populations of nonnative aquatic fauna are abundant in many dryland rivers. Diets of reintroduced river otters were dominated by nonnative aquatic species. Reintroducing semiaquatic carnivores could control nonnative faunal populations. Carnivore reintroduction in the biomic approach to river restoration is promising.